Reassessment of the taxonomic status of Amblyomma cajennense (Fabricius, 1787) with the description of three new species, Amblyomma tonelliae n. sp., Amblyomma interandinum n. sp. and Amblyomma patinoi n. sp., and reinstatement of Amblyomma mixtum Koch, 1844, and Amblyomma sculptum Berlese, 1888 (Ixodida: Ixodidae) - Nava, Santiago (2014)
A reassessment of the taxonomic status of Amblyomma cajennense based on the morphological analyses of ticks from the whole distribution area of the species resulted in the redescription of A. cajennense, the validation of 2 species which had been reduced to synonymy in the past, Amblyomma mixtum and Amblyomma sculptum, and the description and definition of 3 new species, Amblyomma tonelliae n. sp., Amblyomma interandinum n. sp., and Amblyomma patinoi n. sp. This study provides descriptions and redescriptions, scanning electron microscopic and stereomicroscopic images, updated synonymies, information on geographical distributions, and host associations for each of the 6 species. Amblyomma cajennense s.s. is found in the Amazonian region of South America, A. interandinum is reported from the northern part of the Inter-Andean valley of Peru, A. mixtum is present from Texas (U.S.A.) to western Ecuador, A. patinoi occurs in the Eastern Cordillera of Colombia, A. tonelliae is associated with the dry areas of the Chaco region which spans from central-northern Argentina to Bolivia and Paraguay, whereas A. sculptum is distributed from the humid areas of northern Argentina, to the contiguous regions of Bolivia and Paraguay and the coastal and central-western states of Brazil.